Dissipation Behavior of Malathion and DimethoateResidues from the Soil and Their Uptake by Garden Pea(Pisum sativum) - Jondiko, I.O; Getenga, Z.; Wandiga, S.O.; Beck, E. (Environmemental Contamination and Toxicology, 2000)
The contamination of soil by pesticide chemicals can occur through direct application to control some inhabiting insect pests of a variety of economic plants while indirect avenues can occur through aerial applications, spray drifts, wash-off from the atmosphere, treated plants through precipitation, erosion, and run-off from agricultural and forest lands (Mulla et al. 1981). It is obvious, therefore, why a great deal of attention must be paid to studying the many complex interactions that occur between pesticides and the soil (Harvey 1983). The fate of pesticides and their behavior in soil is influenced by several factors including adsorption, movement and decomposition (Shamahat 1980).
Keywords: Dissipation Behavior; Malathion; Dimethoate